2023
DOI: 10.1002/cam4.6170
|View full text |Cite
|
Sign up to set email alerts
|

Umbelliprenin induces autophagy and apoptosis while inhibits cancer cell stemness in pancreatic cancer cells

Abstract: BackgroundUmbelliprenin is a sesquiterpene coumarin isolated from Artemisia absinthium L. and shows antitumor effects in various cancers by inducing apoptosis. However, the antitumor effect of umbelliprenin in human pancreatic cancer has not been clarified.MethodsThe antitumor effects were determined by MTT and AnnexinV/PI double staining assay in vitro and xenograft mice in vivo. Autophagy was determined via immunofluorescence analysis. Apoptotic or autophagic related proteins were measured by immunoblotting.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…In a typical experiment, MDAMB-231 cells treated with 4 μg/mL DOX and PU-SS@DOX, wound healing was inhibited by approximately 18 and 23%, respectively, whereas the control wound recovered about 75% in 48 h, indicating the efficacy of PU-SS@DOX in impairing cellular migration. Further, the in vitro sphere inhibition assay was carried out, as TNBC has a high number of breast cancer stem-like cells (BCSCs), which contribute considerably to the disease’s poor prognosis, metastasis, and relapse . Thus, targeting BCSCs may be a promising strategy for combating TNBC.…”
Section: Resultsmentioning
confidence: 99%
“…In a typical experiment, MDAMB-231 cells treated with 4 μg/mL DOX and PU-SS@DOX, wound healing was inhibited by approximately 18 and 23%, respectively, whereas the control wound recovered about 75% in 48 h, indicating the efficacy of PU-SS@DOX in impairing cellular migration. Further, the in vitro sphere inhibition assay was carried out, as TNBC has a high number of breast cancer stem-like cells (BCSCs), which contribute considerably to the disease’s poor prognosis, metastasis, and relapse . Thus, targeting BCSCs may be a promising strategy for combating TNBC.…”
Section: Resultsmentioning
confidence: 99%
“…Apart from this, umbelliprenin (150) could attenuate cell migration through the Wnt signaling pathway by decreasing the expression levels of Wnt-2, β-catenin, GSK-3β, p-GSK-3β, survivin, and c-myc [193]. In another study, umbelliprenin was found to induce cytoprotective autophagy by reducing the phosphorylation levels of AKT and mTOR and blocking the Akt signaling pathway [230]. In brief, umbelliprenin (150) could exert its antitumor property by inducing apoptosis and autophagy, inhibiting the cell cycle, and attenuating the migration and invasion of cancer cells.…”
Section: Antitumor Effectsmentioning
confidence: 99%
“…Researchers discovered that umbelliprenin (150) could promote apoptosis in tumor cells by annexin V-FITC/PI staining. In the meanwhile, umbelliprenin (150) activated caspase-3, -8, and -9 and the proapoptotic protein Bax and reduced the expression of the antiapoptotic protein Bcl-2, caspase-3, -8, and -9, and the proapoptotic protein Bax and reduced the expression of the antiapoptotic protein Bcl2 [230,231], which promoted apoptosis in the Jurkat T-CLL and Raji B-CLL cell lines in a time-and dosedependent manner [232]. In addition, it could activate the mitochondrial apoptotic pathway and lead to apoptosis of the cancer cells by decreasing the mitochondrial membrane potential, enhancing the P53, P27, P16, and Rb protein expression and diminishing the expression of the proteins of cyclin E, cyclin D, Cdk4, and Cdk6 as well as cell cycle arrest in the G0/G1 phase [233].…”
Section: Antitumor Effectsmentioning
confidence: 99%